Pilot study on the use of art therapy techniques to improve the psycho-emotional state of educational psychologists - Samuratova, Tatigul; Khazhgaliyeva, Gulnar; Makarova, Oksana; Pronkin, Nikolay (Institute of Advanced Engineering and Science, 2025)
The aim of this study is to investigate the impact of art therapy on the psycho-emotional state of educational psychologists. The issue at hand is the prevalence of depression, anxiety, and emotional burnout among future educational psychologists, which can negatively affect their professional performance. To address this problem, the application of art therapy was proposed as a tool to improve the emotional health of students. The experiment involved 107 students aged 20-22 from the Yelabuga Institute of Kazan Federal University. The assessment of emotional state was conducted using the Beck Depression Inventory, the Spielberger-Hanin Anxiety Scale, and the Schreiner, Rosenberg, and Boyko tests. The results indicated that after three months of art therapy, the average level of depression decreased by 15%, anxiety levels decreased by 20%, and emotional burnout was reduced by 15%. Additionally, students’ stress resistance increased by 20%. Thus, art therapy is an effective means for reducing the emotional burden on students. It is recommended to incorporate art therapy techniques into the curricula of universities, colleges, and secondary schools. Further research is necessary to confirm the effectiveness of art therapy among students of various specializations.